The Effects of Valerian Root on Hot Flashes in Menopausal Women - Mirabi, Parvaneh (Shaheed Beheshti University of Medical Sciences, 2013)
Hot flash is among the most common complaints of menopausal women, affecting their career, social activities and quality of life. This study aimed to investigate the effects of Valerian on hot flashes in menopausal women. In this double blind clinical trial, 68 menopausal women with the chief complaint of hot flash were enrolled using sampling at hand and were randomly divided into drug and placebo groups. The women in the drug group were prescribed 255 mg Valerian capsules 3 times a day for 8 weeks. The women in the placebo group were prescribed identical capsules filled with starch. Then, severity and frequency of hot flashes were measured and recorded through questionnaires and information forms in three levels (2 weeks before, four and eight weeks after the treatment). The Severity of hot flashes revealed a meaningful statistical difference pre- and post- Valerian treatment (p <0.001) while this difference was not meaningful in the placebo group. Further, the comparison of the two groups regarding the severity of hot flash after the treatment showed a meaningful statistical difference (p <0.001). Valerian has also led to a reduction of hot flash frequencies 4 and 8 weeks after the treatment (p <0.001) but this difference was not meaningful in drug like group. Valerian can be effective in treatment of menopausal hot flash and that it can be considered as a treatment of choice for reduction of hot flashes among the women who are reluctant to receive hormone therapy due to fear or any other reason.